Developing a Solution Density Analysis Program with Image Processing Technique - Aksoy, Muhittin; Çambay, Zafer; Metin, Serkan (Institute of Economic Development and Social Researches, 2024)
Image processing is a computer program that can be used in many industrial applications, integrated with computers. Image processing consists of a series of operations. These processes begin with the capture of the image, pre-analysis preparations are made with image enhancement techniques, and object detection processes are performed. In this study, information is given about the interpretation of the Elisa microplate prepared in laboratory environments using image processing techniques. The aim of the study; It offers alternative analyzes and syntheses through the image processing program, apart from the ongoing existing analysis methods. It is thought that the analysis of the relevant samples using the image analysis program may be an alternative to the existing detection methods. In addition, it has been shown that thanks to the program, it will be possible to reach more precise information in a shorter time. The fact that the analysis and synthesis stages of the preparations are laid out in a systematic way and the pictures taken from the preparations are easily analyzed clearly show us that image processing techniques have a very important place in the field of health, as in every field in today's technology world. © 2024, Institute of Economic Development and Social Researches. All rights reserved.
Keywords: elisa microplate; image analyse program; Image proccessing